Theoretical calculation guided materials design and capture mechanism for Zn–Se batteries via heteroatom‐doped carbon. Issue 1 (14th July 2022) - Wang, Hongrui; Lai, Kang; Guo, Fangyu; Long, Bei; Zeng, Xianxiang; Fu, Zhiqiang; Wu, Xiongwei; Xiao, Yao; Dou, Shixue; Dai, Jiayu
Abstract: Zinc–selenium (Zn–Se) batteries have generated great research interest because they could potentially meet the requirements of a high‐capacity, high energy density storage device. Unfortunately, efforts to control the shuttle effect of polyselenides have yielded limited success. Nanostructured carbon hosts with nonpolar surfaces have insufficient ability to restrict polyselenides within the cathode. Herein, first‐principles calculations are used to successfully study the merits of heteroatom‐doped graphene as an efficient sorbent with an excellent ability to inhibit the shuttle effect of polyselenides. The calculation results show that using B as a dopant could distinctly enhance interaction between hosts and polyselenides, which occur significant charge transfer with polyselenides and reduce the diffusion energy barrier of Zn ions. Then, we synthesized carbon/Se and boron‐doped carbon material/Se composite cathodes proving that B‐doped carbon could restrict the shuttle effect of polyselenides, which increases the electrochemical performance of Zn–Se batteries. Therefore, the theoretical study identifies a delightful restricted material that could potentially restrict the shuttle effect in Zn–Se batteries and provides a foundation and strategy for the fabrication of long‐life, high‐power‐density Zn–Se batteries. Abstract : According to the first‐principles calculation, B‐doped carbons could occur significant charge exchange with polyselenides and reduce the diffusion energy barrier of Zn ions in zinc–selenium batteries. The test of electrochemical performance demonstrates that B‐doped carbon materials possess a significant restriction effect for the shuttle effect of polyselenides.